Sekiguchi Lesion Gene Encodes a Cytochrome P450 Monooxygenase That Catalyzes Conversion of Tryptamine to Serotonin in Rice - Fujiwara, Tadashi (American Society for Biochemistry and Molecular Biology, 2010)
Serotonin is a well known neurotransmitter in mammals and plays an important role in various mental functions in humans. In plants, the serotonin biosynthesis pathway and its function are not well understood. The rice sekiguchi lesion (sl) mutants accumulate tryptamine, a candidate substrate for serotonin biosynthesis. We isolated the SL gene by map-based cloning and found that it encodes CYP71P1 in a cytochrome P450 monooxygenase family. A recombinant SL protein exhibited tryptamine 5-hydroxylase enzyme activity and catalyzed the conversion of tryptamine to serotonin. This pathway is novel and has not been reported in mammals. Expression of SL was induced by the N-acetylchitooligosaccharide (chitin) elicitor and by infection with Magnaporthe grisea, a causal agent for rice blast disease. Exogenously applied serotonin induced defense gene expression and cell death in rice suspension cultures and increased resistance to rice blast infection in plants. We also found that serotonin-induced defense gene expression is mediated by the RacGTPase pathway and by the Gα subunit of the heterotrimeric G protein. These results suggest that serotonin plays an important role in rice innate immunity.